SOCIAL WELL-BEING, PSYCHOLOGICAL WELL-BEING DAN EMOTIONAL WELL-BEING: STUDI KAUSAL KOMPARATIF PADA PRAKTISI SENI BELA DIRI BIMA DAN KEBUGARAN FISIK - Budiarto, Yohanes (Jurnal Psikologi, 2018)
Individual health promotion includes preventative and curative measures. In the holistic model of public health, the promotion of mental health is an effort that complements the bio-medical approach. Various activities can affect the promotion of mental health is to exercise regularly physical exercise or actively involved in martial arts activities. The positive impacts of joining health clubs as well as martial arts groups to mental health such as increased self-esteem, self-confidence, and subjective well-being have been summarized by many researchers. However, inconsistent results regarding the impact of following the martial arts against the psychological condition of individuals are also found. Some researchers have found that involvement in martial arts increases anti-social attitudes and involvement in violent acts. This study attempts to reveal the phenomenon by conducting a comparative causal study ex post facto on health-care participants in health clubs and BIMA martial arts participants. From the research results obtained the findings that participants BIMA martial arts and sports participants in health clubs have emotional, psychological and social well-being is high. However, only the social well-being participants of the BIMA martial art (M = 4,969, SD = .691) were higher than the club's fitness participants (M = 4.55 3, SD = 1.054); t (58), p = .009.Â Keywords: martial arts, psychological well-being, emotional well-being, social well-being.